FAKTOR YANG MEMPENGARUHI DEBT POLICY PADA PERUSAHAAN SEKTOR CONSUMER GOODS DI INDONESIA - Michelle Fidelia; Nurainun Bangun (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research was to examine the influence of non-debt tax shields, growth, and profitability on debt policy. The population in this research used consumer goods sector companies listed on the Indonesia Stock Exchange during 2018-2020. The design of this research used descriptive study and data retrieval was quantitative. The sampling method used in this research was purposive sampling by determined the criteria. This research used a multiple linear regression and panel data regression with fixed effect model chosen to estimate 34 samples companies. Processing of research data was done using E-Views 12 version software. The results of this research stated that non-debt tax shields and growth have a negative and significant influence on debt policy. Meanwhile, profitability has a positive and insignificant influence on debt policy. This showed that profitability statistically does not affect debt policy in consumer goods sector companies listed on the Indonesia Stock Exchange during 2018-2020.